2007
DOI: 10.1080/10934520701244417
|View full text |Cite
|
Sign up to set email alerts
|

Sludge reduction and volatile fatty acid recovery using microwave advanced oxidation process

Abstract: Sewage sludge was subjected to the combined microwave-hydrogen peroxide-sulfuric acid enhanced advanced oxidation process (MW-H(2)O(2)-H(+)-AOP) to evaluate the potential of reducing suspended solids in sludge. The soluble chemical oxygen demand (SCOD) and acetic acid produced were dependent on the amounts of H(2)O(2) and acid used in the process. For sewage sludge, a higher volume of H(2)O(2) addition not only favored the destruction of sludge solids, but also conserved the carbon content in the medium. Volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Acid also help solublize organic phosphorus and polyphosphate (Chan, et al, 2007). A trend can be seen from Figure 2, where Treatment time highly favours the release of ortho-P, with a slight increase of hydrogen peroxide.…”
Section: Solids Disintegration and Nutrient Releasementioning
confidence: 68%
See 2 more Smart Citations
“…Acid also help solublize organic phosphorus and polyphosphate (Chan, et al, 2007). A trend can be seen from Figure 2, where Treatment time highly favours the release of ortho-P, with a slight increase of hydrogen peroxide.…”
Section: Solids Disintegration and Nutrient Releasementioning
confidence: 68%
“…For the sewage wastewater treatment industry, there are many applications of microwave heating on sludge treatment for reducing volume, improving dewaterability, enhancing digestibility, enhancing nutrient release, pathogen destruction, and stabilizing heavy metal (Menendez, et al, 2002;Liao, et al, 2005;Wojciechowaska 2005;Hong et al, 2006;Eskicioglu et al, 2007;Hsieh et al, 2007;Yu, et al, 2010). It has also been reported that the overall treatment efficiency could be increased with a combination of microwave heating with chemicals (thermo-chemical) for the treatment of sludge (Chan, et al, 2007;Qiao, et al, 2008). The common chemicals used on thermo-chemical process are acid, base and oxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the science behind the many published research articles in this area is novel and has had impact and made significant contributions of knowledge to the scientific community, the background behind the electromagnetic interaction with biomass and wastes has often been overlooked. For [201] MW (80°C) for 5 min and 34 mL/L H2O2 + 17 mL/L H2SO4 Sludge All COD was solubilised [202] MW (80°C), 5 min heating time, with 1 mL H2O2 (30%)/1 %TS dosage WAS 25% increase in SCOD [203] MW (120°C) with 0.80 g H2O2/g dry sludge WAS Optimum parameters for maximum solids' disintegration and nutrient release [204] MW (80°C) for 3 min with 1% H2O2 WAS 18% increase in COD solubilisation [205] MW (120°C) for 10 min with 1 g H2O2 (30 % v/v/ g TS ) WAS COD solubilisation increase from 3% (control) to 24% after pre-treatment. However, no significant effect of combined pre-treatment was observed on methane production and sludge dewaterability [156] MW heating (80°C) followed by addition of H2O2 and then continuous heating to 100°C…”
Section: Discussionmentioning
confidence: 99%
“…When MW/H 2 O 2 -AOP is operated at higher temperatures, the synergistic effect of microwave irradiation and hydrogen peroxide is enhanced. Elevated microwave temperatures (>80°C) increase the decomposition of hydrogen peroxide into hydroxyl radicals and therefore increase the oxidation rate, resulting in a higher degree of solubilisation of the substrate (Eskicioglu et al, 2008;Liao et al, 2007). Lo and Liao (2011) suggested an optimum MW temperature of 120°C for best nutrient recovery and solids disintegration from sludge and dairy manure in a batch mode MW/H 2 O 2 -AOP.…”
Section: Introductionmentioning
confidence: 99%